IMMIGRATION LAW PERSPECTIVE ON FOUNDED CHILD WHO COMPLETE IMMIGRATION CRIME IN INDONESIA - Muhammad Alvi Ghazy Ghazy; Sania Nizar Putri Ashari (Polteknik Imigrasi, 2021)
One of the impacts of the decline in community morale is characterized by the rise of promiscuity which results in more and more babies born out of wedlock. In this regard, the main issue that will be discussed here is the concept of children found from the perspective of immigration law and its implications. According to Islamic law, the child found can be associated with the person who found it by means of confession so that the child found becomes a legitimate child like his own child. Especially for a child found by a girl, guardianship remains with the person who found and recognized it and if the child wants to marry then the guardian is the one who finds and recognizes it. However, its implementation still raises questions about the status of granting immigration documents such as passports or other immigration documents if the child found wants to leave Indonesia.